Institutional and social-economic problems of municipal units management in modern Russia (on materials of the Tambov region) - I. I. Sanzharevsky; V. I. Menshchikova (Путеводитель предпринимателя)
The analysis of a condition of local self-government in modern Russia from a position of institutional and social and economic problems is presented in article. On materials of the Tambov region institutional features of management of municipal units are investigated, problems in the sphere of regulation of powers of local government bodies are revealed and also problems of personnel potential and economic development of municipalities are opened. Questions of the integration of municipal unit in economy of the region and federal programs causing features of management of economic development of municipality are investigated.